Possibilities of Monitoring Unemployment in the NES by Using Unemployment Dynamics Measures (Global Journal of Human-Social Science, 2013)
Employment and unemployment are important subjects that draw attention to participants in economic occurrences of all countries. Monitoring of their dynamics attracts particular attention of the public in transitional countries. Due to numerous particularities accompanying transition, labour market problems in Serbia will continue being the main concern of various economic analyses for a long time. Information on labour market movements is collected and published by the National Employment Service (NES) and the Statistical Office of the Republic of Serbia (SORS). NES gathers and analyzes statistical data from the field of unemployment and employment. Statistical reports of the NES are one of the sources on which basis analysing and monitoring occurrences and tendencies/movements of unemployment and employment in the labour market, their interdependence and relation are performed. They also represent one of the bases for creation and guidance of the Active Employment Policy programme and improvement of unemployment reduction measures.
Keywords: labour market indicators; activity rate; employment rate; unemployment rate; par measures